Pertumbuhan Alometri Dimensi Panjang dan Lingkar Tubuh Sapi Bali Jantan - Sampurna, I Putu; Suatha, I Ketut (Jurnal Veteriner; Vol 11 No 1 (2010), 2010)
Research was conducted at Bukit Jimbaran, Badung Bali from September to October 2007 to investigatethe lenght and circular body dimension of Bali cattle. Ten young male bali cattle 0.5-1.5 year old weremeasured for three times at 2 weeks interval. Collected data was analysed with regretion-corelation byallometric growth lines Y = aXb. F test and coeficient-correlation was then used to chek the validity andacurate models. Result showed that the lenght head, neck, body anterior and posterior had medium potentialgrowth. Circular neck anterior grew early with a high potential. The circular neck posterior growth potentialwas medium, where as circular thorax and abdomen was law poitential growth.
Keywords: allometric long and circular body dimension bali cattle.